Feigned madness in the Greco-Roman world - Hamnett, G (2023)
This thesis presents the first comprehensive treatment of feigned madness as a discrete phenomenon in the Greco-Roman world. I argue that our sources depict feigned madness as a strategy of personal and political resistance to unwelcome structures of power. Individuals feign madness to engage in political and social resistance, to speak freely and to avoid harm. Feigning madness was an especially attractive strategy to the relatively powerless. The phenomenon of feigned madness has not been widely treated in recent scholarship, and this study is the first that attempts to compile and consider a corpus of textual sources (approximately thirty). I discuss significant episodes of feigned madness reported in historical or biographical texts as well as episodes transmitted in verse and myth. The sources are primarily Roman but build on scattered instances in Attic drama. The corpus is dominated by sources from the early Imperial Period (from the end of the first century BCE to the end of the second century CE), which was a time of political transformation characterised by some ancient historians as a period of deliberate deception, hypocrisy and loss of freedom. Stories of feigned madness reflect the perceived political and social reality of the principate and dangers of a tyrannical emperor. This study of feigned madness also offers a more nuanced understanding of ‘real’ madness, by challenging a long-standing view that madmen in the ancient world were typically violent, and that madness brought shame and disenfranchisement on an individual. I use the method of close reading, informed by a variety of scholarly approaches including the history of emotions and the history of medicine.